Outlining the Promotion Strategy of four Moslem Clothing Designers by Comparing the Enthusiasm in Social Media - Destria, Sannaz Dilla; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2013)
Moslem clothing and hijab are undergoing significant growth and is becoming the latest fashion trend in the Indonesian market. Moslem clothing is no longer perceived as being outdated; rather it has become a fashion that is adored and suitable for every Moslem woman. The growth in Moslem fashion is caused by the emergence of many Moslem outfit brands designed by young Indonesian designers. Their products are very loved by the Moslem clothing consumers, not only domestically in Indonesia, but also internationally. Hijabers Community is the largest Moslem community in Indonesia. Many of its members have their own Moslem fashion clothing lines but only three are well known. These brands are Dian Pelangi, Ria Miranda and Jenahara. It is found that social media holds a vital role in boosting the popularity of these three well-known brands.Other members of Hijabers Community have great products but are lacking in popularity. This is because they do not understand how to exploit the social media to promote their products. The three top brands of the Hijabers Community are able to see opportunities from social media marketing that others have not been able to do.Â The aim of this final project is to formulate social media strategy that are adopted from the top four Moslem fashion designers which are Dian Pelangi, Riamiranda, Jenahara, and Shafira. A framework is proposed to help startups of the Moslem Fashion brand to devise a promotion strategy for the social media. The research is conducted by using a comparative study, which compares promotion strategies of the Moslem clothing brand through social media as one of the tools. The comparative study is done by monitoring social media activity in Twitter, Facebook, Instagram, and Google Search. It was found that Dian Pelangi is the most popular brand of the four. Its popularity comes from the fact that the brand was the first-mover in the industry (with regards to young person as the target market) and that it used its time well by taking many roles, in which it has gained many advantages. On top of this, Dian Pelangi is making an excellent use of the social media to promote its product. It was found that the brand has the most number of followers in Facebook, Twitter, and Instagram.Â Keywords: Moslem Clothing, Hijab, Social Media, Promotion Strategy, Comparative Study.